Pengembangan Student Worksheet Model MORE Berbasis Teori Konstruktivistik Sosial Vygotsky di MAN 1 Pontianak - Sutoyo Budiharto; Ismet Basuki (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2021)
This study aims to develop student worksheets of good quality and effectiveness to improve students' knowledge competencies. The student worksheet developed refers to the MORE (Model-Observe-Reflect-Explain) learning model based on Vygotsky's social constructivist theory. This development research refers to the steps developed by Thiagarajan, namely the 4-D model. Data collection techniques in this study applied interviews, observation, and tests. The analysis technique used is descriptive quantitative. The empirical test of increasing knowledge competence uses the pre-experimental method with one group pretest-posttest design. Data on knowledge competency improvement were analyzed using the paired sample t-test. The subjects of this study were students of class X IPS 1 at Moslem Senior High School (MAN). The results of this study are as follows: first, the MORE student worksheet model based on Vygotsky's social constructivist theory has a very good quality. Second, the MORE student worksheet model based on Vygotsky's social constructivist theory is effective for history learning.